If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -2 + 3y = 17 + 12y + -23 Reorder the terms: -2 + 5y + 3y = 17 + 12y + -23 Combine like terms: 5y + 3y = 8y -2 + 8y = 17 + 12y + -23 Reorder the terms: -2 + 8y = 17 + -23 + 12y Combine like terms: 17 + -23 = -6 -2 + 8y = -6 + 12y Solving -2 + 8y = -6 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -2 + 8y + -12y = -6 + 12y + -12y Combine like terms: 8y + -12y = -4y -2 + -4y = -6 + 12y + -12y Combine like terms: 12y + -12y = 0 -2 + -4y = -6 + 0 -2 + -4y = -6 Add '2' to each side of the equation. -2 + 2 + -4y = -6 + 2 Combine like terms: -2 + 2 = 0 0 + -4y = -6 + 2 -4y = -6 + 2 Combine like terms: -6 + 2 = -4 -4y = -4 Divide each side by '-4'. y = 1 Simplifying y = 1
| 3-r=-(3r-6) | | (2x^(4/3))(4x^(5/3))(x^2) | | 9+3x=-21 | | 21/3=-9m | | y-118=-3 | | 9x+24y=27 | | (4)/(5)-12=(3)/(10)x | | -4x-5(x+3)=12 | | 15x-10(-2/15+1/5x)=-1 | | k+9.2=7.6 | | 20x+5y=0 | | -2y=x-10 | | y=x^2-10x+22 | | (4)/(5)-12=(3)/(10) | | 5y-5(2y-6)=15 | | -12x^2+17x+7=0 | | 7.32=13.53+2.81a | | -0.7=-7/9z | | 4(x^3-x+y)=0 | | 5r-19=-47+r | | x^3-21x^2+147x-343=729 | | g=70+3h | | 13m^2-15m=0 | | 5+y=7+y | | -y+138=247 | | 2(8y+7)-16y=14 | | (y+6)2=1 | | 5t/9-3/4=1/12+5t/8 | | 7-10/5 | | 4x^3+22x^2+30x= | | 1-6/5 | | H^2=33-4h |